A New Member of High Field Large Bore Superconducting Research Magnets Family. (April 2019) - Ma, W; Viznichenko, R; Twin, A; Varney, A; Clarke, N; Warren, D; Wotherspoon, R; Hollis, T
Abstract: Over the last 5 years, Oxford Instruments has successfully developed a series of large bore, high field (hence high stored energy) magnet systems, using conventional NbTi and Nb3 Sn low temperature superconductors (LTS). These systems are enabling many new customer applications which have not previously been possible with smaller usable volumes. The magnet systems built to date have cold bores ranging from 150mm to 250mm diameter with central field from 15T to 19T. As well as their use as "outsert" magnets for High Temperature Superconductor (HTS) magnet systems, applications also include Scanning Probe Microscopy (SPM) and dark matter research. In this paper, we will introduce a new member of our high energy magnet system family, with a central field of 12T and cold bore of 320mm incorporating a large field cancellation volume some distance above magnet centre line. We will discuss the challenges which have to be met to provide such magnets, including stress/strain control, quench energy management, coil force and mechanical support.